THE EMOTIONAL INTELLIGENCE AND AGE RELATIONSHIPS TOWARDS BASIC MOVEMENT LOCOMOTOR IN KINDERGARTEN STUDENTS - Pramandhika, Reddy; Rumini, Rumini; Kusuma, Donny Wira Yudha (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
The purpose of this study was to analyze the emotional intelligence relationship towards locomotor basic movement abilities in kindergarten, the age relationship towards locomotor basic movement abilities in kindergarten, the emotional intelligence and age relationship towards locomotor basic movement abilities in kindergarten. This research uses a quantitative approach with correlation design. The sample of this research is 118 students from State Kindergarten Pembina. Data collection techniques used are Scale, Documentation, and Observation. Partial regression test was obtained p-value of 0.032, because the p-value is 0.032 < a (0.05), it is concluded that there is a significant influence between the emotional intelligence ability with locomotor basic movement in kindergarten. Age factors significantly influence the locomotor basic movement in kindergarten. This is evidenced by the partial regression test, a 0.040 < a (0.05) p-value is obtained. Based on the simultaneous regression test, the p-value is 0.045. Because the p-value is 0.045 < a (0.05), it is concluded that there is a significant influence between the emotional intelligence and age ability with locomotor basic movement in kindergarten. It can be concluded that there is a relationship between the emotional intelligence ability towards locomotor basic movement in kindergarten. There is a relationship between age and locomotor basic movement in kindergarten. There is a relationship between emotional intelligence ability and age on locomotor basic movement in kindergarten.